Energy metabolism of growing blue foxes, Alopex lagopus - Koskinen, Nita; Tauson, Anne-Helene (Via Celoria 2 - 20133 MilanoDipartimento di Scienze Animali, Università degli Studi di Milano, 2010)
As a strictly seasonal animal the blue fox exhibits seasonal fluctuations in feed intake and accretion of body fat, feed intake and body fat retention being very high during autumn and early winter while fed unrestrictedly. In practice blue foxes are fed ad libitum during the growing - furring period both those aimed for pelting and the future breeding stock. Selective breeding has focused on producing heavy animals and meanwhile reproductive performance has declined among yearling vixens. Very little is known about the energy requirements of blue foxes during different life stages and the impact of season on the energy metabolism. The main objective of this project was to establish baseline data on the energy requirement of growing blue foxes by measuring feed intake, energy expenditure, and protein and fat retention. The data will be used to develop practical farming feeding recommendations for young future breeding blue fox vixens, in order to avoid excessive fat retention during the autumn, and then severe weight reduction during the winter. v 2010 ok